Altered brain responses in subjects with irritable bowel syndrome during cued and uncued pain expectation. Issue 1 (3rd November 2015) - Hong, J.‐Y.; Naliboff, B.; Labus, J. S.; Gupta, A.; Kilpatrick, L. A.; Ashe‐McNalley, C.; Stains, J.; Heendeniya, N.; Smith, S. R.; Tillisch, K.; Mayer, E. A.
Abstract: Background: A majority of the subjects with irritable bowel syndrome (IBS) show increased behavioral and brain responses to expected and delivered aversive visceral stimuli during controlled rectal balloon distension, and during palpation of the sigmoid colon. We aimed to determine if altered brain responses to cued and uncued pain expectation are also seen in the context of a noxious somatic pain stimulus applied to the same dermatome as the sigmoid colon. Methods: A task‐dependent functional magnetic resonance imaging technique was used to investigate the brain activity of 37 healthy controls (18 females) and 37 IBS subjects (21 females) during: (i) a cued expectation of an electric shock to the abdomen vs a cued safe condition; and (ii) an uncued cross‐hair condition in which the threat is primarily based on context vs a cued safe condition. Key Results: Regions within the salience, attention, default mode, and emotional arousal networks were more activated by the cued abdominal threat condition and the uncued condition than in the cued safe condition. During the uncued condition contrasted to the cued safe condition, IBS subjects (compared to healthy control subjects) showed greater brain activations in the affective (amygdala, anterior insula) and attentional (middle frontal gyrus) regions, and in the thalamus and precuneus. These disease‐related differences were primarily seen in female subjects. Conclusions & Inferences: The observed greater engagement of cognitive and emotional brain networks in IBS subjects during contextual threat may reflect the propensity of IBS subjects to overestimate the likelihood and severity of future abdominal pain. Abstract : When there was no specific cue about the occurrence of abdominal pain stimulus, IBS subjects had increased brain responses in multiple affective, sensory, and cognitive brain regions compared to healthy subjects. These findings suggest that IBS subjects overestimate the likelihood of pain stimuli and engage brain networks involved in affective and sensory processing.